Analisis Kesalahan Ejaan pada Karangan Mahasiswa Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Dharma Pontianak - Pabianus Simon (Syntax Idea)
The study focused on the misspelling of Indonesian in the essay of a student of the accounting course, the department of economics and business, Widya Dharma Pontianak University. The method used in this study is a descriptive analysis. The data in this study would be spelling mistakes, whereas the data source would be by a two-semester student group that attended an Indonesian course. As for the results, there are 10 misspelling spelling capitals, 3 misspelling spelling, 5 misspelling of root, 9 miswriting of root words, 2 miswriting syllables, 4 syllables, 1 writership errors, 5 writes point marks, 1 writes errors of comma, 1 writes hyphen, and 1 omission of writing hyphen. Based on the study, it is expected that the professor emphasized the EYD technique in Indonesian college and always trained the students to spell it correctly so that the student's writing could fit the writing code. In addition, students are expected to have an Indonesian love soul so that they can write well from different study programs.